Ξ − atomic X-ray spectroscopy using a counter-emulsion hybrid method. (25th November 2022) - Fujita, M; Ekawa, H; Endo, Y; Goto, R; Hasegawa, S; Hayakawa, S H; Hayashi, K; Honda, R; Hoshino, K; Hosomi, K; Ichikawa, M; Ichikawa, Y; et al.
Abstract: Ξ − atomic X-ray spectroscopy is one of the most useful methods for investigation of the Ξ–nucleus strong interaction. Since the X-ray energy is shifted and/or broadened due to the Ξ–nucleus strong interaction compared to those calculated from electromagnetic interaction alone, the measurement of the energy shift, Δ E, and the width, Γ, give us information on the Ξ–nucleus potential. A serious problem in the measurement is the significant background derived from in-flight Ξ − decay. A novel method of identifying stopped Ξ − events using the nuclear emulsion was developed to realize the first Ξ − atomic X-ray spectroscopy experiment as the J-PARC E07 experiment, which also aimed at searching for ΛΛ and Ξ − hypernuclei in the emulsion. The X-rays emitted from Ξ − Br and Ξ − Ag atoms were measured using germanium detectors. No clear peaks were observed in the obtained spectra. However, we succeeded in reducing the background to 1/170 by this method employing coincidence measurements using nuclear emulsion and X-ray detectors.